2010
DOI: 10.1007/s12206-010-0926-y
|View full text |Cite
|
Sign up to set email alerts
|

Examination of flame length for burning pulverized coal in laminar flow reactor

Abstract: Because there has been a recent increase in the use of low calorific coal compared to standard coal, it is crucial to control the char flame length governing the burning life-time of coal in a coal-fired utility boiler. The main objective of this study is to develop a simplified model that can theoretically predict the flame length for burning coal in a laboratory-scale entrained laminar flow reactor (LFR) system. The char burning behavior was experimentally observed when sub-bituminous pulverized coal was fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…This distance is usually yellowish in color, showing the release of the volatiles prior to the initial ignition stage. The luminous, bright, and thick flame segment next to the coal ignition stage signified complete oxidation of volatiles, whereas the remaining tail of the flame with rather weak luminosity was denoted as char combustion. , The quantitative method for three combustion stages is further detailed in Figure S2 of the SI. A MotionPro Y3 high-speed camera from IDT coupled with microscale lens was employed to analyze individual burning particles, including their velocities, volatile cloud sizes, and ignition times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This distance is usually yellowish in color, showing the release of the volatiles prior to the initial ignition stage. The luminous, bright, and thick flame segment next to the coal ignition stage signified complete oxidation of volatiles, whereas the remaining tail of the flame with rather weak luminosity was denoted as char combustion. , The quantitative method for three combustion stages is further detailed in Figure S2 of the SI. A MotionPro Y3 high-speed camera from IDT coupled with microscale lens was employed to analyze individual burning particles, including their velocities, volatile cloud sizes, and ignition times.…”
Section: Methodsmentioning
confidence: 99%
“…The luminous, bright, and thick flame segment next to the coal ignition stage signified complete oxidation of volatiles, whereas the remaining tail of the flame with rather weak luminosity was denoted as char combustion. 15,16 The quantitative method for three combustion stages is further detailed in Figure S2 particles, including their velocities, volatile cloud sizes, and ignition times. The detailed method for calculating particle velocities has been previously described 17 and in also detailed in Figure S3 of the SI.…”
Section: Introductionmentioning
confidence: 99%
“…However, OH-PLIF is usually limited owing to its narrow field-of-view, which is difficult for the investigation on the entire flame range from ignition to the end of single-particle volatile combustion of coal particle streams . Various optical diagnostic techniques (OH-PLIF, CH*, C 2 * chemiluminescence, two-color or three-color pyrometer, shadow Doppler particle analyzer, and laser Doppler velocimetry) were employed to comprehensively study the ignition and combustion of particle streams. With an optical particle-sizing pyrometer, Shaddix from Sandia Laboratory measured the joint temperature–size statistics of size-classified burning pulverized coal chars. He indicated that O 2 -enriched combustion significantly increased the char surface temperature and reduced the char burnout time.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 38% of the world's electricity is produced from coal, and since 2000, global coal consumption has grown faster than that of any other fuel. Asian countries, including Japan, Chinese Taipei, and Korea, import significant quantities of steam coal for electricity generation [1,2]. Coal blending, one of the many uses of coal, introduces various coals to the power generation industry, especially to increase the use of low-rank coal.…”
Section: Introductionmentioning
confidence: 99%